1,3-Dibromo-5,5-dimethylhydantoin as promoter for glycosylations using thioglycosides - Xu, Fei-Fei; Pereira, Claney L.; Seeberger, Peter H. (Beilstein Journal of Organic Chemistry, 2017)
1,3-Dibromo-5,5-dimethylhydantoin (DBDMH), an inexpensive, non-toxic and stable reagent, is a competent activator of thioglycosides for glycosidic bond formation. Excellent yields were obtained when triflic acid (TfOH) or trimethylsilyl trifluoromethanesulfonate (TMSOTf) were employed as co-promoters in solution or automated glycan assembly on solid phase.
Keywords: automated glycan assembly; 1,3-dibromo-5,5-dimethylhydantoin; glycosylation; promoter; thioglycosides